Implementasi Satuan Pendidikan Aman Bencana (SPAB) dalam Meningkatkan Kesiapsiagaan Guru PAUD di Kabupaten Pangandaran - Nandhini Hudha Anggarasari; Estin Nofiyanti; Noer Laelly Barorroh Taufik Abdul Ghofur (Abdimas Indonesian Journal, 2026)
Pangandaran Regency is a region with a relatively high level of disaster vulnerability, thus requiring systematic efforts to improve the preparedness of teachers and early childhood education (PAUD) communities. This study aims to implement the Disaster Safe Education Unit (SPAB) program to improve the preparedness of PAUD teachers and Posyandu cadres in Pangandaran Regency. The program is implemented through a series of activities including SPAB socialization, education on early detection assessments of child development, identification of disaster risk areas, creation of evacuation maps, formation of evacuation teams, development of evacuation SOPs, and disaster simulations. The study involved 64 participants consisting of PAUD teachers and Posyandu cadres in Pangandaran Regency. The results showed a significant increase in SPAB understanding (from 14% to 98%), mastery of child development assessments (95%), understanding of disaster risk areas (from 75% to 98%), and teacher ability in educating children about disasters (increasing from 95% with no experience to 45% able to practice). The SPAB program has proven effective in building awareness and preparedness for disasters at the early childhood education level. The successful implementation was supported by multi-stakeholder engagement, local policy support, and a strategic partnership with the Regional Disaster Management Agency. This program can serve as a sustainable model for strengthening disaster literacy in early childhood and the resilience of educational communities